Военная техника: раздел тома "Техника" / редакторы: И. Кудрявцева, И. Русецкая - Аксенова Мариам (2000)
Экземпляры: (20181005) / Инвентарный номер: 37749 / Цена: 38.20 / Сис.шифр: 68.8я2 / Авт.знак: В 63 / ББК: 68.8я2